2011
DOI: 10.1007/s00221-011-2693-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential integration of visual and kinaesthetic signals to upright stance

Abstract: The present experiment was designed to assess the effect of active (deliberate) maintenance of a small forward (FL) or backward body lean (BL) (about 2° ankle flexion) with respect to the spontaneous direction of balance (or neutral posture, N) on postural balance. We questioned whether BL and FL stances, which impose a volitional proprioceptive control of the body-on-support angle, could efficiently reduce mediolateral displacements of the centre of pressure (CoP) induced by the visual motion of a room and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…We computed the Root Mean Square (RMS) of the CoP in both mediolateral and anteroposterior directions as an indicator of the individual's stability. Indeed, the RMS provides the information about the variability of the CoP in space [15]. We computed the Fast Fourier Transform (FFT) of the CoP and the correlation with a 0.25Hz sinus so as to evaluate coupling between the postural response and the moving visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…We computed the Root Mean Square (RMS) of the CoP in both mediolateral and anteroposterior directions as an indicator of the individual's stability. Indeed, the RMS provides the information about the variability of the CoP in space [15]. We computed the Fast Fourier Transform (FFT) of the CoP and the correlation with a 0.25Hz sinus so as to evaluate coupling between the postural response and the moving visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…We designed a sensorimotor experimental setup to assess the sensory integration of each participant. The setup has been used in several studies [36,37]. It evaluates (1) the effect of a moving virtual visual room on postural control and (2) one's capability to use proprioceptive information to reduce visual dependency [36,37].…”
Section: Methodsmentioning
confidence: 99%
“…The setup has been used in several studies [36,37]. It evaluates (1) the effect of a moving virtual visual room on postural control and (2) one's capability to use proprioceptive information to reduce visual dependency [36,37]. It has been shown that the integration of proprioceptive cues differs among individuals in unstable posture [38][39][40].…”
Section: Methodsmentioning
confidence: 99%
“…First, we used the Sensory Profile (SP) and the Adolescents/Adults Sensory Profiles (AASP) developed by Dunn [11], [12] to assess Movement, Visual, Touch, and Auditory processing. Second, we designed an experimental setup to assess the effect of a moving virtual visual scene (VVS) on postural control, and the individual's capability to use proprioceptive inputs provided in dynamics of balance to reduce visual dependency [13].…”
Section: Methodsmentioning
confidence: 99%